SAT0263 Neoplasia in patients with systemic lupus erythematosus in spain: relesser registry data. (15th June 2017) - Urruticoechea-Arana, A; Rua-Figueroa, I; Martín-Martínez, MA; Alonso, F; Lόpez-Longo, J; Galindo-Izquierdo, M; Olivé, A; Calvo, J; Fernández-Nebro, A; Pego-Reigosa, JM; ,
Abstract : Background: There is limited evidence on the risk of neoplasia in autoimmune diseases such as systemic lupus erythematosus. Objectives: The objective of this study is to analyze the incidence of cancer in the Spanish population with SLE and the factors associated in its development: RelesSER Registry Data. Methods: We calculated the incidence density of malignant neoplasms, the standardized incidence ratio and the average time to develop the first neoplasm after diagnosis of SLE in patients of the SLE registry of the Spanish Rheumatology Society (RelesSER) fulfilling ACR97 criteria. We carried out a bivariate analysis of the associated factors to neoplasms and multivariate by logistic regression. Results: A total of 3607 patients (90.4% female) were included. We registered 140 neoplasms in women (4.3%) and 14 in men (4%) (p<0.821). Incidence density 7.3/1000 patient-years (95% CI:4.85–10.98) (7.39 in patient-years women and 6.93 in men) without significant differences. After stratification by gender and age, cancer appeared in 3.2% of the women aged under 45 versus 3.8% of the men; 4.1% of women aged 45–65 years versus 5.9% of men and a 5.3% of women 65 and older versus 2.5% of men the same age. The standardized incidence ratio (SIR) was 2.16; 1.51 in men and 2.38 in women, highest for women under 65 years old. The SIR for >65 years was 0.98; 0.59 in men and 1.55 in women. The average time until de development of the first malignant neoplasm was 10 years (RI:5.75–17.00), being lower in women [9.5 (RI: 5.00–17.0) years] than in men [12.5 (8.75–17.5)] and in patients under 45 years versus over 45 years [8.0 (RI: 5.00–16.00)]. Malignant neoplasms were the cause of death in 10% of the patients (15/154), predominantly hematological and breast cancers, both at 19% followed by lung cancer in 14.3%. Factors associated to malignant neoplasms in the bivariate analysis are shown in (table 1 ). No immunosuppressive therapy was associated with the development of neoplasms. In the multivariate model, adjusted for age and time of disease duration, age was the only significant variable (OR:1.030; 95% CI: 1.003–1.059; p=0.029) with a trend for ACE inhibitors use (OR:1.866; 95% CI: 0.808–4.306; p=0.144), SLEDAI (last visit) (OR: 0.904; 95% CI: 0.806–1.015; p=0.089, SLICC/ACR DI) (without neoplasias) (OR: 1.160; 95% CI: 0.961- 1.401; p=0.123), and duration of the disease in months (OR: 1.003; 95% CI: 1.000–1.006; p=0.068). Conclusions: The incidence of neoplasia in Spanish women with SLE is higher than expected for age and gender. Malignant neoplasms were the cause of death in 10% of the patients, predominating hematological and breast cancers followed by lung cancer. Acknowledgements: The RelesSER registry has been supported by the FIS (ISCIII) - European Regional Development Fund (FEDER), fellowship PI11/02857. It has also been partially funded by: GSK, UCB, Roche and Novartis. Disclosure of Interest: None declared